STUDY OF FACTORS INFLUENCING THE ACCEPTION OR REJECTION OF TUBAL LIGATION FOR CONTRACEPTION - M. Sarram; T. Kamran; M. Moshirfatemi & J. Azimi (Tehran University of Medical Sciences, 1976)
In Isfahan tubal ligation project was initiated in July 1970. A total of 310 women, referring to the University of Isfahan Health Center and or admitted to the Arnin Maternity Hospital, were interviewed for tubal ligation procedure. Thirty six patients rejected tubal ligation and 274 women accepted. Of the latter group 114 patients did not refer later on. A total of 160 tubal ligations were performed. A. total of 181 women from all groups were interviewed for the second time on a 1ater date. The reason for acceptance, rejection or refusal of tubal ligation was discussed with them during the second interview. Correlation between personal and social characteristics of cases with acceptance and rejection of tubal ligation were made. Fear from operation, worries about future outcome and religious behavior were the most important factors causing rejection of tubal ligation. Having enough children, physical weakness, financial problems were the most important reasons given for acceptance of tubal ligation. Suggestions are made for using this information in future tubal ligation programs in Iran.